Education And Training of Bengawan Solo Water Cleaning Using Filtration Method in Karanggeneng Village, Karanggeneng District, Lamongan Regency - Mima Mimatun Nasihah; Nur Lathifah Syakbanah; Gading Wilda Aniriani; Andini Dwi Magfiroh (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
The northern part of Lamongan Regency is an area that is geologically and geographically vulnerable to freshwater. The condition of the existing water sources is not suitable for use as a source of clean water, because the water is brackish and green in color. The eutrophication process occurs due to excessive use of fertilizers for pond business, so that the nitrogen and phosphate content is high. The community in Karanggeneng village uses water from the Bengawan Solo River for daily use. The water condition of Bengawan Solo in the rainy season is dark brown in color because it contains a lot of soil, while in the dry season it is green because it contains a lot of pesticide or fertilizer residues discarded by farmers. From the problems above, it is necessary to socialize the water purification of Bengawan Solo by using the filtration method. Socialization activities are carried out directly to the Karanggeneng village community. This activity is carried out in two stages, the first is the preparation of tools and materials, the second stage is socialization to the community. In the first stage, chemical and physical water quality parameters were tested. In the second stage, the community was very enthusiastic about the implementation of this activity. The use of filtration methods is easy and inexpensive to be applied on a household scale. Suggestions, it is necessary to disseminate information to the wider community so that all people can access clean water for their daily needs. the second stage is socialization to the community. In the first stage, chemical and physical water quality parameters were tested. In the second stage, the community was very enthusiastic about the implementation of this activity. The use of filtration methods is easy and inexpensive to be applied on a household scale. Suggestions, it is necessary to disseminate information to the wider community so that all people can access clean water for their daily needs. the second stage is socialization to the community. In the first stage, chemical and physical water quality parameters were tested. In the second stage, the community was very enthusiastic about the implementation of this activity. The use of filtration methods is easy and inexpensive to be applied on a household scale. Suggestions, it is necessary to disseminate information to the wider community so that all people can access clean water for their daily needs.